The complete book of textures for artists : step-by-step instructions for mastering more than 275 textures in graphite, charcoal, colored pencil, acrylic, and oil - Pearce, Steven (Artist); Howard, Denise J.; Tavonatti, Mia (Walter Foster Publishing, 2020)
Learning to render a variety of textures is a fundamental skill for any fine artist, no matter the chosen media or subject matter. The Complete Book of Textures for Artists features 501 step-by-step lessons, tips, and techniques for rendering a wide range of textures in a variety of media, including graphite pencil, charcoal, colored pencil, oil, and acrylic. After an introduction to the basic tools and materials, discover a variety of drawing and painting techniques, such as hatching, crosshatching, shading, blending, layering, burnishing, and more. From there, you will learn just how easy it is to render everything from wood, metals, glass, food, and water to human and animal textures, such as hair, skin, fur, eyes, and more. Each page features easy-to-follow steps demonstrating how to create each specific texture. You will discover tips and techniques for reproducing certain textures in a variety of media, as well as how to create physical textures in your artwork. Whether you're an experienced artist or just starting out, The Complete Book of Textures for Artists features a wide variety of both traditional and contemporary techniques. Organized into sections based on subject matter and media, each technique is presented with simple instructions and beautiful examples. Not only will you learn a variety of techniques, but you'll also discover new ideas and inspiration for using the techniques in your own projects. Packed with easy-to-follow instructions and plenty of helpful artist tips, The Complete Book of Textures for Artists is the perfect resource for beginning and established artists who are ready to master the intricacies of texture in their artwork.